WAYS OF PRACTICAL TRAINING MODERNIZATION OF THE FUTURE COMPUTER SCIENCE TEACHERS - Vlasii, Olesia (Mountain School of Ukrainian Carpaty, 2021)
Training of future teachers in higher education is a complicated and complex process, which includes the study of disciplines of psychological and pedagogical, special and methodological cycle of disciplines, as well as the practice of various types. In the article, the main features of practical training of future computer science teachers under the conditions of education functioning in a digital society, are analyzed. It is emphasized that practical training of students should become a cross-cutting line of student learning and should be realized continuously throughout the whole study process at higher educational institution. It is proposed to attribute practical training not only to the practice of different kinds, but also to the practical tasks during the study of disciplines of psychological and pedagogical, special and methodical cycles, as well as during course, qualification and master's work. The ways of modernization and improving of practical training of future computer science teachers are proposed based on a close cooperation of higher and secondary educational institutions. Importance of developing educational software by students for using it in learning process at a secondary school provided by modern techniques, innovative pedagogical and information technologies is established. Practical training of students in HEIs is one of the most important components of the process of methodical training of future teachers, which becomes a link between theoretical training and future professional activity. Тhe intensive growth of the digital society's demand for qualified specialists requires the integration of practical training of students at all stages of education in the HEI, which will improve the formation of general and professional competencies, and continuity of practical training will increase motivation to learn and willingness to work in the real world.